Sharing Spaces and Entanglements With Big Cats: The Warli and Their Waghoba in Maharashtra, India - Nair, Ramya; Dhee; Patil, Omkar; Surve, Nikit; Andheria, Anish; Linnell, John D. C.; Athreya, Vidya (Frontiers in Conservation Science, 2021)
The interplay between humans and wildlife in shared spaces are complex phenomena that have mainly been explored through techno-managerial standpoints and focused on the damages caused by interactions. However, humans relate to the large, potentially dangerous wildlife that they share space with within complex ways rooted in their own cultural and societal context. Our study explores the institution of ‘Waghoba,’ a big cat deity worshipped by the Indigenous Warli community in Maharashtra, India. The Warli cosmology allows people to view big cats holistically, rather than through the binaries of modern taxonomy, such that Waghoba being the form of both the tiger (Panthera tigris) and leopard (Panthera pardus) or wagh as it is locally known. We document the presence of 150 shrines dedicated to this deity across our study site. The Warli strongly believe that conducting the ‘required’ rituals for Waghoba will protect them from the negative impacts of sharing spaces with big cats. Such beliefs make space for a shared blame and reciprocal relationship between Waghoba, the animal, and the people themselves. Such relationships facilitate sharing spaces as the humans that live in the landscape already have a predisposed cultural relationship with the species, making acceptance easier. This is relevant for present-day wildlife conservation because such traditional institutions are likely to act as tolerance-building mechanisms embedded within the local cosmology. Further, it is vital that the dominant stakeholders outside of the Warli community (such as the Forest Department, conservation biologists, and other non-Warli residents who interact with leopards) are informed about and sensitive to these cultural representations because it is not just the biological animal that the Warlis predominantly deal with.